Abonamiento orgánico en el rendimiento en verde de Pisum sativum L. var. Verde en Santiago de Chuco, La Libertad - Ibañez Pereda, Liliana Elizabeth (2019)
This research work was carried out in the hamlet Huamada, district and province of Santiago de Chuco, with the objective of evaluating the green yield of the pea crop (Pisum sativum L.) by applying three organic fertilizers. The completely randomized block design (DBCA) was used, with 4 treatments (T0-control, T1-compost, T2-guinea pig manure and T3-cow dung), in 4 blocks and 16 experimental units. The variables evaluated were plant height, number of pods per plant, pod length, pod width, number of grains per pod, weight of 100 pea grains, yield in green (Kg. Ha-1). It is concluded that the best performance is obtained with the T2 manure treatment (4 t.ha-1) with an average of 9. 5753 kg.ha-1.